2005
DOI: 10.1111/j.1369-7625.2005.00343.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of self‐management programmes in caring for people from culturally and linguistically diverse backgrounds in Melbourne, Australia

Abstract: Background Chronic disease self-management programmes are now an important adjunct to the treatment and care of Australians with chronic illnesses. Most programmes are delivered in English and cater for ÔAngloÕ views of health and illness. The Peer-Led Self-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 32 publications
1
37
0
2
Order By: Relevance
“…Other researchers who have utilised focus group methodologies note that participants may fail to attend at the allotted time (Caperchione et al, 2011;Walker et al, 2005). This was also observed in this study where, despite agreeing to attend, many students failed to attend the focus groups.…”
Section: Problems Will Attendance and Participationsupporting
confidence: 52%
See 1 more Smart Citation
“…Other researchers who have utilised focus group methodologies note that participants may fail to attend at the allotted time (Caperchione et al, 2011;Walker et al, 2005). This was also observed in this study where, despite agreeing to attend, many students failed to attend the focus groups.…”
Section: Problems Will Attendance and Participationsupporting
confidence: 52%
“…Focus groups were initially selected as they allow for the exploration of group norms, values and attitudes, in an informal group discussion setting (Neuman, 2009;Newburn, 2012). They are particularly useful for promoting discussion within discrete cultural groups and among participants with lower literacy levels (Henderson & Kendall, 2011;Walker, Weeks, McAvoy, & Demetriou, 2005). The utilisation of focus groups and interviews was practical due to the oral nature of Sudanese communication; individuals are more likely to reveal their experiences orally, and via a social gathering, which the dynamic interaction of focus groups and, to some extent, interviews allows (Caperchione, Kolt, Tennent, & Mummery, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…The services offered by the CHOs in our study are typically provided in English thus limiting access for people who are not proficient in English. An imperative exists for self‐management support initiatives that are accessible in other languages and meet different cultural sensitivities (Walker et al. 2005).…”
Section: Discussionmentioning
confidence: 99%
“…19 However, in a study with multiple ethnic groups such as Vietnamese, Chinese, Italian and Greek in Australia, the authors reported that CDSMP might not produce good outcomes for all ethnic groups due to cultural differences. 20 Among Korean populations, the applicability of a generic, selfefficacy-enhancing intervention such as CDSMP is not well known.…”
Section: Theoretical Frameworkmentioning
confidence: 99%